ANALISIS KUALITAS HIDUP PASIEN SKIZOFRENIA FASE STABIL YANG MENDAPATKAN TERAPI ANTIPSIKOTIK KOMBINASI RISPERIDON DAN HALOPERIDOL DI INSTALASI RAWAT JALAN RSUD KOJA JAKARTA UTARA - Wolo, Mulya Adjaib Riwu; Julaeh, Julaeh; Luthfiana , Farisa (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
uality of life is a complex aspect and is an important parameter in planning treatment for chronic diseases, one of which is schizophrenia. Mental health is a condition where an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can deal with pressure, can work productively, and is able to contribute to his community. Schizophrenia is a psychiatric disease that shows a chronic, heterogeneous syndrome, including strange and disorganized thoughts, delusions, hallucinations, and failure in psychosocial functioning. Antipsychotics are the mainstay of treatment. Antipsychotics are effective in treating “positive symptoms” in acute episodes (e.g. hallucinations, delusions, passivity phenomena) and preventing relapse. Typical and atypical antipsychotics are equally effective in treating positive symptoms, but have different side effect histories. The results of the study showed that Risperidone is an effective antipsychotic with minimal side effects of extrapyramidal syndrome compared to conventional high potency antipsychotics (Haloperidol). Risperidone is better for treating negative symptoms in schizophrenia than Haloperidol. Haloperidol works as an antipsychotic by increasing the brain's dopamine exchange cycle.